Reactive power control and performance analysis of doubly fed induction generatorin micro grid - Syed Sarfaraz Nawaz; Sandipam Tara Kalyani (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
For both financial and environmental considerations, the power system includes a large number of solar and wind generating plants. In reality, wind energy has always been used using a doubly fed induction generator (DFIG) based variable speed wind turbine. This study examines the effectiveness of indirect control of a doubly fed induction generator for closed loop reactive power adjustment. A wind energy conversion system with continuous grid power's design, analysis, and MATLAB simulation are also covered. For DFIG to work reliably and be controlled to ensure stability for the power system, a seamless transition mode change is required. The horizontal axis wind turbine technology provides the necessary reactive power into the grid under all unexpected circumstances. The concept of DFIG mathematical modelling is covered. Various simulated outputs at loading circumstances are shown, along with separate control of active and reactive powers and variations in prime mover speed and excitation. This study examines the performance enhancement of DFIG using its grid-based proportional integral (PI), proportional integral derivative (PID), and fractional order proportional integral derivative (FOPID) controllers. Based on the thorough simulation findings, the type of control system that gives the efficient performance of DFIG in grid is ultimately decided. These simulation results demonstrate how the suggested controllers outperform the current controllers in terms of improving system performance.